Rancang Bangun Aplikasi Bekafe Untuk Membantu Menghubungkan Customer Kopi Dan Kafe Di Seluruh Indonesia Berbasis Android - Albert Arapenta Sembiring; Muhammad An Naufal Langnegara; Hoga Saragih (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Bina Insani, 2022)
The coffee shop business is one of the rapidly growing business industries in Indonesia. This encourages many people to open coffee shops or develop existing coffee shops. Bepahkupi creates a better coffee shop ecosystem in Indonesia by building an Android-based Bekafe application. This application helps connect coffee shops and coffee customers. With one application, the information and connection between the two parties is greatly facilitated. The Android-based Bekafe application is specifically designed to make it easier for customers to find cafe locations. In addition, customers will also get information about operational schedules, routes/locations and cafe menus. Blackbox method is testing the fundamental aspects of the system without paying attention to the internal logical structure of the software. Starting from the login page, home, cafe, shop, cart, notification, and maps work well with VALID results on every test. In addition, the authorss chose the User Acceptance Test (UAT) in the stages of the testing process. UAT is done by asking a number of respondents to operate the Bekafe application. The results of testing on the Bekafe application get good results. Almost all respondents gave satisfactory results. Although the test results were satisfactory, the respondents gave additional suggestions to complete the Bekafe application. As for what can be added, news features about coffee or cafes in Indonesia, delivery features, and updating the UI and UX appearance of the Android-based Bekafe application